The influence of four-month exercises during lessons on body posture in children in younger school age - Kot, Kamila; Kokosz, Mirosław; Stencel-Gabriel , Krystyna (Journal of Education, Health and Sport, 2018)
The aim of the study was to check the impact of the school environment on the child's body posture and assessment of the influence of four-month physical exercises on school children's lessons on the results of measurements of spine mobility, physiological spinal curvature and attitude of the body Material and methods: the study group consisted of 23 children (including 10 boys), a control group of 15 children (including 10 boys), pupils of the 1st and 2nd grade Sports Primary School in Sosnowiec. The body posture was assessed 2 times at a 4-month interval in both groups (test and control). Spine mobility was examined by a finger-floor test and left and right using a centimeter, the physiological curvature of the spine was examined at the top of the sacrum using a goniometer , shoulder settings and thoracic kyphosis were examined by the Kasperczyk method.Conclusion: The conducted observational study indicates a positive clinical effect of the, introduced during, lesson exercises with children in order to promote the correct posture.